Digestibility of Dry Matter, Organic Matter and Protein of Pellet Feed Using Indigofera Flour (Indigofera sp) in Superior Balitnak Chickens (KUB) - Kowel, Youdhie H.S.; Imbar, Meity R; Waleleng, Poula O.V. (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
This study aims to evaluate the consumption of dry matter, organic matter, digestibility of dry matter, organic matter, and protein of pellet feed in KUB chickens containing indigofera flour (Indigofera sp). The method used was a completely randomized design with three treatments and six replications: (P1) commercial pellets, (P2) pellets with 5% indigofera flour, and (P3) pellets with 10% indigofera flour. A total of 18 chickens aged 10 weeks were placed randomly in individual cages. The results showed that indigofera (Indigofera sp) flour can be used up to 10% in the pellet ration of KUB chickens without reducing the digestibility of dry matter, organic matter, and protein.